INTERSYSTEM INTERCOMMUNICATIONS OF INDEXES OF ELECTRIC ACTIVITY AND CEREBRIL HEMODYNAMIC OF CEREBRUM WITH NEUROSIS STAMMER - Васильєва, Н.О.; Shmaley, S.V. (World of Medicine and Biology, 2012)
The substantial differences of electric activity and circulation of blood in the left hemisphere of boys are set with a nevrosis stammer. The boys of preschool age with a nevrosis stammer had considerably anymore positive and negative meaningful and high cross-correlation connections between indexes base-line EEG and REG from all possible cross-correlation connections, that testifies to tension of the regulator systems of organism.
Keywords: neurosis stammer; cerebral blood stream; electric activity of cerebrum; boys of preschool age